The Role Of The Prosecutor's Office As A State Attorney In Resolving State Administrative Disputes At The Batuah Market In Banjarmasin City - Zafirah; Bahran (Interdisciplinary Explorations in Research Journal, 2023)
Abstract Referring to the Prosecutor's Office Law Number 11 of 2021 concerning the Prosecutor's Office, one of the roles of the Prosecutor's Office is as a State Attorney who acts as a mediator or facilitator in disputes or disputes between State Institutions, Central / Regional Government Agencies and BUMN / BUMD in the fields of Civil and State Administration. In accordance with Attorney General Regulation Number 7 of 2021 concerning Guidelines for the Implementation of Law Enforcement, Legal Assistance, Legal Consideration, Other Legal Actions, and Legal Services in the Civil and State Administration Sector. One of the Legal Assistance carried out by the Banjarmasin State Attorney's Office is in the settlement of State Administration Disputes at Batuah Market, Banjarmasin City. Keywords: Role of the Prosecutor's Office, State Attorney, Dispute, State Administration Abstrak Mengacu pada Undang-Undang Kejaksaan Nomor 11 Tahun 2021 tentang Kejaksaan, salah satu peran Kejaksaan adalah sebagai Pengacara Negara yang berperan sebagai mediator atau fasilitator dalam perselisihan atau sengketa antar Lembaga Negara, Instansi Pemerintah Pusat/Daerah dan BUMN/BUMD di bidang Perdata dan Tata Usaha Negara. Sesuai dengan Peraturan Jaksa Agung RI Nomor 7 Tahun 2021 tentang Petunjuk Pelaksanaan Penegakan Hukum, Bantuan Hukum, Pertimbangan Hukum, Tindakan Hukum Lain, dan Pelayanan Hukum di Bidang Perdata dan Tata Usaha Negara. Salah satu Bantuan Hukum yang dilakukan oleh Kejaksaan Negeri Banjarmasin adalah dalam penyelesaian Sengketa Tata Usaha Negara di Pasar Batuah Kota Banjarmasin. Kata Kunci: Peran Kejaksaan, Jaksa Pengacara Negara, Sengketa, Tata Usaha Negara